An improved dynamic model for a single-phase generator based on three-phase cage rotor induction machine - Liyanage, D.; Rajakaruna, Sumedha (2015)
© 2015 IEEE. An improved dynamic model for recently introduced single-phase induction generator based on a three-phase cage rotor induction machine is presented in this paper. In this generator topology one of the three windings of three-phase induction generator is used as the excitation control winding and remaining two windings connected in series are used as the output winding. The dynamic model of this single-phase generator system presented in some papers is based on a few assumptions which are not adequately represented the machine. In improved mathematical model, the non linear behavior of magnetizing reactance in the saturated region and the effect of core resistance have been taken into account. The comparison of experimental and simulation results confirms that the improved dynamic model is much more accurate than the existing model.